PENAFSIRAN RASYID RIDHA DAN M. QURAISH SHIHAB TENTANG PERNIKAHAN BEDA AGAMA - Nasution, Rahmi Padilah; Ikhwan, Muhammad; Rahman, Yenni; Rahmad, Mardikola Tri (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2022)
This research is motivated by the fact that there are differences in interpretation of the understanding of the Ahl al-Kitab which causes marriage problems in it. This research aims to find out the interpretation of Rashid Rida and M. Quraish Shihab regarding the understanding of Ahl al-Kitab, as well as a comparative analysis of the interpretation between Rasyid Ridha and M. Quraish Shihab regarding marriages between Muslim men and women of the Ahl al-Kitab. This type of research is library research. The interpretation method used is the Muqaran method by comparing the Tafsir al-Manar by Rasyid Ridha with the Tafsir al- Misbah by M. Quraish Shihab in QS al-Maidah/5:5 by using an interpretive approach, as well as books that have relevance to the problem at hand. discussed, then review and conclude.According to Rasyid Ridha in his book Tafsir al-Manar, it is explained that what is meant by ahl al-Kitab in the Qur'an is not only Yahudi and Nasrani, but he includes religions that have holy books in which the teachings of monotheism are contained. This is based on Q.S an-Nahl verse 36, that Allah sent messengers from all people, it's just that their holy book along with the times has changed and is even lost to time. Meanwhile, M. Quraish Shihab argues that the Ahl al-Kitab group in the Qur'an is only focused on Yahudi and Nasrani, apart from that they are not included in the ahl al-Kitab.